Musclin prevents depression-like behavior in male mice by activating urocortin 2 signaling in the hypothalamus - Ataka, Koji; Asakawa, Akihiro; Iwai, Haruki; Kato, Ikuo (Frontiers in Endocrinology, 2023)
Introduction: Physical activity is recommended as an alternative treatment for depression. Myokines, which are secreted from skeletal muscles during physical activity, play an important role in the skeletal muscle-brain axis. Musclin, a newly discovered myokine, exerts physical endurance, however, the effects of musclin on emotional behaviors, such as depression, have not been evaluated. This study aimed to access the anti-depressive effect of musclin and clarify the connection between depression-like behavior and hypothalamic neuropeptides in mice. Method: We measured the immobility time in the forced swim (FS) test, the time spent in open arm in the elevated-plus maze (EPM) test, the mRNA levels of hypothalamic neuropeptides, and enumerated the c-Fos-positive cells in the paraventricular nucleus (PVN), arcuate nucleus (ARC), and nucleus tractus solitarii (NTS) in mice with the intraperitoneal (i.p.) administration of musclin. Next, we evaluated the effects of a selective corticotropin-releasing factor (CRF) type 1 receptor antagonist, selective CRF type 2 receptor antagonist, melanocortin receptor (MCR) agonist, and selective melanocortin 4 receptor (MC4R) agonist on changes in behaviors induced by musclin. Finally we evaluated the antidepressant effect of musclin using mice exposed to repeated water immersion (WI) stress. Results: We found that the i.p. and i.c.v. administration of musclin decreased the immobility time and relative time in the open arms (open %) in mice and increased urocortin 2 (Ucn 2) levels but decreased proopiomelanocortin levels in the hypothalamus. The numbers of c-Fos-positive cells were increased in the PVN and NTS but decreased in the ARC of mice with i.p. administration of musclin. The c-Fos-positive cells in the PVN were also found to be Ucn 2-positive. The antidepressant and anxiogenic effects of musclin were blocked by central administration of a CRF type 2 receptor antagonist and a melanocortin 4 receptor agonist, respectively. Peripheral administration of musclin also prevented depression-like behavior and the decrease in levels of hypothalamic Ucn 2 induced by repeated WI stress. Discussion: These data identify the antidepressant effects of musclin through the activation of central Ucn 2 signaling and suggest that musclin and Ucn 2 can be new therapeutic targets and endogenous peptides mediating the muscle−brain axis.